Protein Adsorption Patterns and Analysis on IV Nanoemulsions—The Key Factor Determining the Organ Distribution - Mirko Jansch; Rainer H. Müller; Cornelia M. Keck (Pharmaceutics, 2012)
Intravenous nanoemulsions have been on the market for parenteral nutrition since the 1950s; meanwhile, they have also been used successfully for IV drug delivery. To be well tolerable, the emulsions should avoid uptake by the MPS cells of the body; for drug delivery, they should be target-specific. The organ distribution is determined by the proteins adsorbing them after injection from the blood (protein adsorption pattern), typically analyzed by two-dimensional polyacrylamide gel electrophoresis, 2-D PAGE. The article reviews the 2-D PAGE method, the analytical problems to be faced and the knowledge available on how the composition of emulsions affects the protein adsorption patterns, e.g., the composition of the oil phase, stabilizer layer and drug incorporation into the interface or oil core. Data were re-evaluated and compared, and the implications for the in vivo distribution are discussed. Major results are that the interfacial composition of the stabilizer layer is the main determining factor and that this composition can be modulated by simple processes. Drug incorporation affects the pattern depending on the localization of the drug (oil core versus interface). The data situation regarding in vivo effects is very limited; mainly, it has to be referred to in the in vivo data of polymeric nanoparticles. As a conclusion, determination of the protein adsorption patterns can accelerate IV nanoemulsion formulation development regarding optimized organ distribution and related pharmacokinetics.